Inequality in Intercollegiate Athletics - Andrew Zimbalist (Journal of Intercollegiate Sport, 2013)
In this paper, the author provides an overview of economic inequality in intercollegiate athletics, tracing it from its origins in the late 19th century, through home rule, the introduction of the NCAA’s national broadcasting policy and its subsequent regionalization after Oklahoma v. NCAA, conference realignments, RSNs, the BCS and NCAA distribution policies. The paper argues that the current economic situation and the growing inequality is unsustainable and that policies to reverse the course are necessary. Policies to moderate inequality will not only assist in promoting financial stability but will also blunt the all-out drive to win and thereby help to reestablish the primacy of education in intercollegiate athletics.